Perancangan Sistem Informasi Kerja Praktek dan Tugas Akhir Berbasis Website Pada Program Studi Teknik Industri ITEBA Menggunakan Pendekatan Data Flow Diagram (DFD) - Pane, Amirah Nova Khairiyah; rumapea, Elsa Sri Erjuni; Azzahra, Fadhilla; Anugrah, Ibnu; Maulidina, Siti Nur; Gucci, Dinda Okta Dwi Yanti Ridwan; Pertiwi, Elsa Putri (Fakultas Teknik, Universitas Riau Kepulauan, 2025)
The administrative process of Kerja Praktek (KP) and Tugas Akhir (TA) in the Industrial Engineering Department ITEBA is still conducted manually, which often causes problems in registration, data recording, student progress monitoring, and communication between students, supervisors, and coordinators. This study aims to design a web-based information system to support more efficient, transparent, and structured KP and TA management. The method used is system modeling with the DFD approach and implemented with Glide App. The results produced an information system with key features such as online registration, document upload, progress monitoring, dashboards for students, supervisors, and coordinators, document archiving. Functionality testing showed that all features operated as required, while user satisfaction surveys indicated that 85% students, 90% supervisors, and 80% coordinators felt that the system improved convenience, efficiency, and transparency in KP and TA process. These findings indicate that the system successfully addresses manual administration issues and serves as a foundation for the future development of broader digital academic system.